Determining the Microbial Source of Methane Production in Anaerobic Digestion Systems Through High-Throughput Sequencing Technology - Yang, Bin; Wang, Changmei; Zhao, Xingling; Liu, Jianfeng; Yin, Fang; Zhang, Wudi (Frontiers in Energy Research, 2022)
Anaerobic digestion is widely used to simultaneously generate biogas while treating different organic wastes. It is difficult to determine the source of CH4 from the complex microbial community structure using traditional microbiological pure culture techniques. Therefore, this study aimed to elucidate the microbial source of CH4 in low-temperature anaerobic digestion systems using the recently developed high-throughput sequencing technology. Herein, anaerobic digestion microbes were domesticated at 15°C and then inoculated into pig manure-containing raw materials in a batch anaerobic digester to form a low-temperature anaerobic digestion system with fermentation controlled at 15°C. Several analytical approaches including abiotic factor analysis and biotic factor analysis (high-throughput sequencing) were applied to investigate the abiotic factors, bacterial communities, and archaeal communities in the low-temperature anaerobic digestion system. The results showed that: 1) The anaerobic digestion lasted for 120 days, with 68.65 L total gas production and 31.19 L CH4 production. 2) The relative abundances of the primary and secondary dominant bacterial operational taxonomic units ranged from 8.02 to 22.84% and 5.62–17.09%, respectively, with 99% similarities to Clostridium cellulovorans (a typical cellulose- and hemicellulose-degrading bacterium) and Terrisporobacter petrolearius (a representative fermentation bacterium), respectively. Moreover, the relative abundance of the primary dominant methanogenic archaeal operational taxonomic unit ranged from 1.03 to 16.85%, with 98% similarity to Methanobacterium beijingense, which is a typical hydrogenotropic methanogen. Based on the low-temperature CH4-producing metabolic pathways of bacterial and methanogenic operational taxonomic units, Methanobacterium beijingense was found to be the primary functional microbe for CH4 production in the 15°C anaerobic digestion system.